Employee Handling Techniques Towards Enhancement of Customer Service at Giligans SM Fairview Quirino Hi-way Quezon City: A Tool for Crafting a Guide: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Good customer service involves providing courteous and quick service to meet customers'needs during their dining experience. Restaurant owners can encourage this kind of goodservice by honoring employees who are exceptionally gifted in this area and having them trainothers. Customers who can see managers, supervisors, and waiter staff are more likely togive employees the opportunity to provide good customer service by making requests. Beingvisible also helps customers feel they are having a better experience by showing that they areright there to help.This reveals that the handling technique employed by Giligans is a quick response to thecustomer. Engaging in active listening in order to make that person feel truly heard,understood, and served and to give great customer service to the restaurant server needs tobe able to listen to what the customer wants. Some issues encountered by the respondentswere wrong orders, spilled glasses of water, problems with the food, encountering rudecustomers, and children running when served. It was handled by management by apologizingto the guest for the wrong order, giving a genuine apology, taking the food and feedback to thekitchen, responding with an apology and a solution, and last talk to the parents of the childrento avoid running.Employees should maintain their quick responses and listen actively to acquire information.Employees should always be ready for unexpected situations and ready to give solutions.Employers must have strategies for boosting employees' confidence and morale and allowingthe employees to personalize their own space. In terms of children running when you serve,employees should talk to the parents of children to avoid accidents that may be caused.
Keywords: Business